Gut microbiota regulates innate anxiety through neural activity of medial prefrontal cortex in male mice - Ren, Jing; Lian, Xiao-Ying; Ye, Wan-Qian; Wen, You-Lu; Lu, Cheng-Lin; Cao, Xiong (Frontiers in neuroscience, 2025)
Innate anxiety, a stable personality trait conceptualized as trait anxiety, represents a fundamental dimension of individual differences in emotional regulation. Clinical evidence and animal studies indicate that elevated innate anxiety significantly increases susceptibility to psychiatric disorders. While the gut microbiota has been increasingly recognized as a critical modulator of neuropsychiatric health, its specific contribution to innate anxiety has yet to be fully elucidated. We investigated gut microbiota contributions to innate anxiety in mice using stratified behavioral phenotyping in the elevated plus maze (EPM), antibiotic (ABX)-mediated microbiota depletion, fecal microbiota transplantation (FMT), c-FOS staining, transcriptomic profiling, and vivo fiber photometry. We found that innate high-anxiety (HA) and low-anxiety (LA) mice exhibited distinct gut microbial compositions. Microbiota depletion induced significant anxiolytic effects, while FMT from HA donors recapitulated anxiety-like behaviors. Neural activation mapping revealed elevated c-FOS expression in the medial prefrontal cortex (mPFC), basolateral amygdala (BLA), and central amygdala (CeA) of HA-FMT recipients. Transcriptomic analysis of mPFC tissue in HA- and LA-FMT recipients demonstrated microbiota driven regulation of transcriptional reprogramming, protein modification, and synapse modulation, indicating mechanistic connections along the microbiota gut-brain axis. Fiber photometry confirmed heightened mPFC neuronal activity during innate anxiety states in HA-FMT mice. Our findings establish that gut microbiota modulates innate anxiety through mPFC neural activity, providing novel insights into microbiome-based interventions for anxiety.